2016
DOI: 10.1016/j.jcct.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

3D printing based on cardiac CT assists anatomic visualization prior to transcatheter aortic valve replacement

Abstract: Background 3D printing is a promising technique that may have applications in medicine, and there is expanding interest in the use of patient-specific 3D models to guide surgical interventions. Objective To determine the feasibility of using cardiac CT to print individual models of the aortic root complex for transcatheter aortic valve replacement (TAVR) planning as well as to determine the ability to predict paravalvular aortic regurgitation (PAR). Methods This retrospective study included 16 patients (9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
127
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(129 citation statements)
references
References 27 publications
1
127
0
1
Order By: Relevance
“…Some recent studies have shown the applications of 3D printing in cardiovascular disease, such as coronary artery disease, aortic and pulmonary venous valve disease 8, 9, 10, 11, 12. 3D printing technology also allows for the production of individualised cardiac stents to reduce the rate of in‐stent re‐stenosis 1…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have shown the applications of 3D printing in cardiovascular disease, such as coronary artery disease, aortic and pulmonary venous valve disease 8, 9, 10, 11, 12. 3D printing technology also allows for the production of individualised cardiac stents to reduce the rate of in‐stent re‐stenosis 1…”
Section: Introductionmentioning
confidence: 99%
“…Deployment of the same device into the 3D model as implanted in the patient was reported to improve anticipation of potential difficulties and to have the potential to help minimize peri- and post-operative complications [7]. More recently, we reported the use of flexible 3D printed models of the aortic root complex derived from routine TAVR planning CT angiography to predict perivalvular leak in a small series of patients [11]. 3D printed models of the implanted valves (26 or 29 mm Edwards SAPIEN XT in this patient series) with a closed configuration and corresponding to the valve implanted in each patient were carefully positioned in the patient’s printed aortic root model.…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%
“…[18][19][20] Similarly, good to excellent agreement has been reached between 3D printed models and original source 2D images for dimensional measurements of aortic valve, aortopulmonary artery, and aortic aneurysms. [21][22][23][24][25] However, in a recent study, Ho et al have indicated that the variances in aortic diameter measurements between 3D printed models and 2D contrastenhanced CT images exceeded 1.0 mm, which is beyond the standard deviation of 1.0 mm. 26 This highlights the potential limitations of using anatomic landmarks to measure accuracy of 3D printed hollow models, such as heart models or aneurysmal models.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the accuracy of 3D printed models of cardiovascular disease with good to excellent correlation between 3D printed models and original CT or MRI data. [21][22][23][24][25] However, these studies are limited in assessment of diameter changes in the selected anatomical regions, which failed to consider the whole shapes of vascular structures or aneurysms. Further, according to a recent systematic review, majority of the current studies compared 3D printed models with original source CT or MRI data, 12,[21][22][23][24] while only a few of them compared images of the scanned 3D printed models with original source imaging data (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation